TRANSCENDENCE-BASED PROTECTION OF CHILDREN IN CONFLICT WITH THE LAW AFTER DIVERSION - Azharniyah, Anna; Wardiono, Kelik; Absori; Budiono, Arief (Veredas do Direito, 2026)
Protection of children in conflict with the law is a constitutional mandate that demands a sustainable process, not only during the formal diversion phase but also throughout the post-diversion phase. This study aims to analyze the urgency of reconstructing the post-diversion protection model for children in conflict with the law, which has tended to have minimal state oversight and been entirely borne by the family. Using a constructivist paradigm and critical legal studies methods, this study explores the integration of the transcendental dimension as an instrument of inner supervision to prevent recidivism. The results show that the post-diversion phase is a crucial transition period in which spiritual values ​​such as repentance, remembrance of God (zikir), and parental role models (uswatun hasanah) serve as the foundation for psychological rehabilitation that fills the gap in positive legal instruments. This model transforms the diversion agreement from a mere administrative contract into a sacred moral bond that strengthens the child's integrity through a prophetic approach.